The diurnal cycle of clouds and precipitation at the ARM SGP site: Cloud radar observations and simulations from the multiscale modeling framework. Issue 14 (26th July 2017) - Zhao, Wei; Marchand, Roger; Fu, Qiang
Abstract: Millimeter Wavelength Cloud Radar (MMCR) data from December 1996 to December 2010, collected at the U.S. Department of Energy Atmospheric Radiation Measurement (ARM) program Southern Great Plains (SGP) site, are used to examine the diurnal cycle of hydrometeor occurrence. These data are categorized into clouds (−40 dB Z e  ≤ reflectivity < −10 dB Z e ), drizzle and light precipitation (−10 dB Z e  ≤ reflectivity < 10 dB Z e ), and heavy precipitation (reflectivity ≥ 10 dB Z e ). The same criteria are implemented for the observation‐equivalent reflectivity calculated by feeding outputs from a Multiscale Modeling Framework (MMF) climate model into a radar simulator. The MMF model consists of the National Center for Atmospheric Research Community Atmosphere Model with conventional cloud parameterizations replaced by a cloud‐resolving model. We find that a radar simulator combined with the simple reflectivity categories can be an effective approach for evaluating diurnal variations in model hydrometeor occurrence. It is shown that the MMF only marginally captures observed increases in the occurrence of boundary layer clouds after sunrise in spring and autumn and does not capture diurnal changes in boundary layer clouds during the summer. Above the boundary layer, the MMF captures reasonably well diurnal variations in the vertical structure of clouds and light and heavy precipitation in the summer but not in the spring. Key Points: A radar simulator combined with the simple reflectivity categories can be an effective approach for model evaluations The MMF only marginally captures observed increases of boundary layer clouds after sunrise in spring and autumn, but not in summer The MMF captures reasonably well diurnal variations in the vertical structure of clouds and precipitation above the boundary layer in summer